Does Travel Time to a Radiation Facility Impact Patient Decision‐Making Regarding Treatment for Prostate Cancer? A Study of the New Hampshire State Cancer Registry. (11th November 2016) - Ghali, Fady; Celaya, Maria; Laviolette, Michael; Ingimarsson, Johann; Carlos, Heather; Rees, Judy; Hyams, Elias
Abstract: Purpose: We sought to determine whether further distance from a radiation center is associated with lower utilization of external beam radiation therapy (XRT). Methods: We retrospectively identified patients with a new diagnosis of localized prostate cancer (CaP) within the New Hampshire State Cancer Registry from 2004 to 2011. Patients were categorized by age, D'Amico risk category, year of treatment, marital status, season of diagnosis, urban/rural residence, and driving time to the nearest radiation facility. Treatment decisions were stratified into those requiring multiple trips (XRT) or a single trip (surgery or brachytherapy). Multivariable regression analysis was performed. Results: A total of 4, 731 patients underwent treatment for newly diagnosed CaP during the study period, including 1, 575 multitrip (XRT) and 3, 156 single‐trip treatments. Of these, 87.6% lived within a 30‐minute drive to a radiation facility. In multivariable analysis, time to the nearest radiation facility was not associated with treatment decisions ( P = .26). However, higher risk category, older age, married status, and winter diagnosis were associated with XRT ( P < .05). More recent year of diagnosis and urban residence were associated with single‐trip therapy (primarily surgery) ( P < .05). There was a significant interaction between travel time and season of diagnosis ( P = .03), as well as a marginally significant interaction with urban/rural status ( P = .07). Conclusion: Overall, further travel time to a radiation facility was not associated with lower utilization of XRT. These data are encouraging regarding access to care for CaP in New Hampshire.